Pengaruh Profitabilitas, Ukuran perusahaan, Good Corporate Governance dan Peluang Investasi terhadap Nilai Perusahaan - Fina Wardah Fitriyah; Anis Wulandari; Yudha Sambharakreshna (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2023)
This research was conducted with the aim of knowing the variables of good corporate governance, profitability, company size, investment opportunities that affect the variable value of the company. Manufacturing Companies in the Basic Industry and Chemical Sector Listed on the Indonesia Stock Exchange for the 2016-2021 period are the objects of this research. Determining the number of research samples using purposive sampling method. The selected samples were analyzed by means of multiple regression analysis then subjected to classical assumption tests and partial hypothesis testing. Based on the results of multiple regression analysis and hypothesis testing, it shows that the audit committee variable has no effect on firm value, while the variables of managerial ownership, institutional ownership, independent board of commissioners, profitability, company size, and investment opportunities have an influence on firm value